PROSPEK BISNIS BANTEN : UPAYA MENGURANGI MENTAL KOMSUMTIF DAN KEMISKINAN DI BALI - NYOMAN SRI MULYANI (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Upakara is part of yadnya or offerings aimed at realizing harmony. The ceremony is also called Dewa Yadnya pujawali. Wali said that the philosophical symbolic meaning of offerings that are representative of the contents of the universe created by Ida Sang Hyang Widhi. Changes in lifestyle of the people of Bali from the agricultural industry has changed the order of Balinese life. Activities Bali increasingly complex society in the form of cultural activities, jobs, and others so that women no longer Bali always worked together to make offerings or sajen, but had to buy to residents who are experts offerings. There are several factors that led to the buying public offerings, namely (1) the factors bustle society, (2) factors of public knowledge, (3) social factors kemasyarakat, (4) factors of business opportunities keuntungam, (5) factors sradha bhaki, (6) the factors globalization, (7) the geographic factors and facilities, and (8) factor of chance.